Correlation between Digital Literacy and Teaching Efficacy among Teachers in Private Medical Colleges in Shandong Province - Li, Ping; Liu, Chao; Qi, Wenqian; Wang, Xin; Liu, Mengmeng; Guo, Hongting (Education Insights, 2026)
This study investigated the current status and relationship between digital literacy and teaching efficacy among teachers in private medical colleges in Shandong Province, with the aim of providing an empirical basis for targeted faculty development. A total of 345 full-time teachers from five private medical colleges were surveyed using an adapted DigCompEdu digital literacy scale and the Tschanen-Moran Teacher Efficacy Scale. Descriptive statistics, group difference testing, Pearson correlation analysis, and multiple linear regression were conducted using SPSS 27.0. The overall mean score for digital literacy was 3.57 ± 0.62, and the overall mean score for teaching efficacy was 3.78 ± 0.61, indicating moderate-to-high levels in both constructs. Within digital literacy, technical application scored highest (3.68 ± 0.72), whereas data literacy was relatively weak (3.45 ± 0.68). Within teaching efficacy, classroom management achieved the highest score (3.92 ± 0.65), while student engagement was lowest (3.68 ± 0.71). Digital literacy was significantly and positively correlated with teaching efficacy (r = 0.68, p < 0.01). Regression analyses further showed that all dimensions of digital literacy significantly predicted teaching efficacy, with instructional innovation (β = 0.44, p < 0.001) and technical application (β = 0.38, p < 0.001) exerting the strongest effects. Male teachers, those with 5–20 years of teaching experience, and professors reported higher scores. These findings highlight the need for systematic digital competence training, enhanced resource support, and incentive mechanisms to promote the coordinated improvement of digital literacy and teaching efficacy in private medical education.